Pemikiran Islam: Studi Perbandingan Konsep Pemikiran Abdurrahman Wahid dan Hassan Hanafi - M Sabiq Rohmatulloh; Muhammad Ardy Zaini (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
Abstract: The thought of a theologian or philosopher will have a great influence on his followers in concrete life. Because as the basis of religion, reason or theology will be the basis of behavior and spirit in life itself. So we need a concept of thought that is not only selfish but also humane. This study aims to describe the differences and similarities of the concepts of thought of Abdurrahman Wahid and Hassan Hanafi. This research is a library research with a qualitative descriptive method. Literary research is the search for a set of scientific literature, books, documents and various reports related to the problem to be solved. This study uses a comparative literature approach with Damono's theory. The data collection techniques used in this study were documentation techniques, reading techniques, and note-taking techniques. Qualitative analysis with presentation of metadata. Data obtained by the literature study method. The data in this study were analyzed describing the similarities and differences. The results of this study indicate that there are differences and similarities in the concept of thought among Islamic phenomenological figures, namely Abdurrahman Wahid and Hassan Hanafi. Abdurrahman Wahid's research findings can be said to be related to efforts to preserve and preserve the heritage and practice of Islamic culture. Meanwhile, Hassan Hanafi also reconstructs a liberal and independent Islamic culture, through "Mawqifuna min al-turrets al-qadi" which reforms Islamic thought by reviving and rebuilding classical sects so that they are not outdated and useful for this era.